2007
DOI: 10.1623/hysj.52.6.1316
|View full text |Cite
|
Sign up to set email alerts
|

Lake Victoria: derivation of a corrected natural water level series /Lac Victoria: dérivation d'une série naturelle corrigée des niveaux d'eau

Abstract: Lake Victoria water levels provide an important indicator of climate; since 1954 these levels have been maintained natural by agreement, but after recent increased releases require adjustment to retain a naturalised series. It is possible to compute the impact of recent over-abstraction on declining water levels. This impact has been significant: of the order of 0.6 m.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
37
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(41 citation statements)
references
References 4 publications
4
37
0
Order By: Relevance
“…This rate of decline was about 50% less than the observed rate of decline. These findings were similar with the findings for Lake Victoria reported by Sutcliffe and Petersen () who found that the observed lake levels declined, but the reconstructed lake levels remained unaltered if abstractions from a power plant station were excluded from the water balance.…”
Section: Discussionmentioning
confidence: 99%
“…This rate of decline was about 50% less than the observed rate of decline. These findings were similar with the findings for Lake Victoria reported by Sutcliffe and Petersen () who found that the observed lake levels declined, but the reconstructed lake levels remained unaltered if abstractions from a power plant station were excluded from the water balance.…”
Section: Discussionmentioning
confidence: 99%
“…The White Nile's main water source is Lake Victoria, which gains more than 80% of its water from direct rainfall (Di Baldassare et al, 2011). The Lake's level has exhibited high variability in response to rainfall variation and extreme rainfall events (Conway, Allison, Felstead, & Goulden, 2005) and also more recently due to management factors, such as regulation of lake outflows for electricity generation (Conway, 2005;Sutcliffe & Petersen, 2007). The other 20% of the water inputs to the lake derive from tributary inflows, including the Kagera and Mara Rivers.…”
Section: Climate Change and Water Resources In The Equatorial Nile Basinmentioning
confidence: 99%
“…Severe droughts occur approximately every 3-4 years during the short rains, every 7-8 years during the hot dry season (December, January, and February), and every 5-8 years during the long rainy season (Awange et al 2008). Lake Victoria is mainly rain-fed with direct precipitation accounting for approximately 80% of the water inflow to the lake (Sutcliffe and Petersen 2007), and about 10% coming from five main tributaries, with the Kagera River being the main contributor. The remaining 10% comes from various small tributaries.…”
Section: The Study Area and Data Set Descriptionsmentioning
confidence: 99%